2017
DOI: 10.1177/1525822x17710640
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Cognitive Effort and Response Quality of Question Formats in Web Surveys Using Paradata

Abstract: Measuring attitudes and opinions employing agree/disagree (A/D) questions is a common method in social research because it appears to be possible to measure different constructs with identical response scales. However, theoretical considerations suggest that A/D questions require a considerable cognitive processing. Item-specific (IS) questions, in contrast, offer contentrelated response categories, implying less cognitive processing. To investigate the respective cognitive effort and response quality associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 21 publications
3
59
0
4
Order By: Relevance
“…We often interpret longer response latencies and the presence of the behavioral indicators we measured as signs of cognitive response difficulty (e.g., Bassili and Scott 1996;Schaeffer and Dykema 2011). However, recent theorizing and evidence suggests these outcomes may be desirable when comparing AD and CS questions (Höhne and Lenzner 2018;Höhne et al 2017). Because CS questions use construct-specific response categories, which will likely vary on a questionby-question basis in a battery, they encourage deeper processing, which will increase processing time and likely result in respondents producing other behaviors when attempting to respond in an optimal manner.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We often interpret longer response latencies and the presence of the behavioral indicators we measured as signs of cognitive response difficulty (e.g., Bassili and Scott 1996;Schaeffer and Dykema 2011). However, recent theorizing and evidence suggests these outcomes may be desirable when comparing AD and CS questions (Höhne and Lenzner 2018;Höhne et al 2017). Because CS questions use construct-specific response categories, which will likely vary on a questionby-question basis in a battery, they encourage deeper processing, which will increase processing time and likely result in respondents producing other behaviors when attempting to respond in an optimal manner.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Liu et al (2015) reported extreme response style was present for both AD and CS formats based on latent class factor analysis. Finally, in a web survey comparing questions presented stand-alone or in grids, Höhne et al (2017) reported no differences between AD and CS questions for data quality as indicated by nondifferentiation and dropping out of the survey before completion.…”
Section: Experimental Evidence Comparing Ad and Cs Questionsmentioning
confidence: 95%
See 2 more Smart Citations
“…Ключевые слова: когнитивная нагрузка; мультимодальная оценка когнитивной нагрузки, связанной с проведением интервью; PAPI и CAPI; качество опросных данных; шкала Пааса; частота сердечных сокращений 1 ВОПРОСЫ ИСТОРИИ, ТЕОРИИ И МЕТОДОЛОГИИ Величина когнитивной нагрузки на интервьюера и респондента при проведении опроса -ключевой компонент оценки затрачиваемых ими когнитивных ресурсов и умственных усилий, который позволяет не только локализовать потенциальные источники ошибок измерения или учесть риски использования интервьюерами или респондентами стратегий, минимизирующих усилия и время заполнения в ущерб качеству данных, но и выбирать оптимальные форматы вопроса [11], управлять эффектами социальной желательности [17] или планировать оптимальное сочетание способов проведения опроса (например, телефонное интервью, онлайн-опрос и т.д.) и технических решений, касающихся, в частности, использования компьютерных технологий в сборе данных [см., напр.…”
unclassified